Women, we need to be courageous - Munyabugingo, Illuminée (Torture Journal, 2018)
My name is Illuminée Munyabugingo. The 1994 genocide against Tutsis happened when I was thirty-four years old. I was born in Kigali in a camp for internally displaced persons. My family had moved there from Eastern Province because of the 1959 massacres of Tutsis. We were a family with sixteen children. During the 1959 massacres, the house of my family was not destroyed as it was during the 1994 genocide. People still had kindness when I was younger.